Synthesis of carbon‐14 and stable isotope labeled Avagacestat: a novel gamma secretase inhibitor for the treatment of Alzheimer's disease. (5th September 2014) - Burrell, Richard C.; Easter, John A.; Cassidy, Michael P.; Gillman, Kevin W.; Olson, Richard E.; Bonacorsi, Samuel J.
<x xml:space="preserve">Abstract</x> Bristol‐Myers Squibb and others are developing drugs that target novel mechanisms to combat Alzheimer's disease. γ‐Secretase inhibitors are one class of potential therapies that have received considerable attention. (R)‐2‐(4‐Chloro‐N‐(2‐fluoro‐4‐(1, 2, 4‐oxadiazol‐3‐yl)benzyl)phenylsulfonamido)‐5, 5, 5‐trifluoropentanamide (Avagacestat) is a γ‐secretase‐inhibiting drug that has been investigated by Bristol‐Myers Squibb in preclinical and clinical studies. An important step in the development process was the synthesis of a carbon‐14‐labeled analog for use in a human absorption, distribution, metabolism, and excretion study and a stable isotope labeled analog for use as a standard in bioanalytical assays to accurately quantify the concentration of the drug in biological samples. Carbon‐14 labeled Avagacestat was synthesized in seven steps in a 33% overall yield from carbon‐14 labeled potassium cyanide. A total of 5.95 mCi was prepared with a specific activity of 0.81 μCi/mg and a radiochemical purity of 99.9%. 13C6‐Labeled Avagacestat was synthesized in three steps in a 15% overall yield from 4‐chloro[13C6]aniline. A total of 585 mg was prepared with a ultraviolet purity of 99.9%.